RESEARCH ON SIZE EFFECT OF COMBINED ROTOR CONSIDERING MICROCRACK - ZHU ZhuoPing; WANG AiLun; SHAO ShiCong; LIU XiangJun (Jixie qiangdu)
During the process of combined rotor modularization amplification or reduction,due to the size effect,the law of the influence of microcrack expansion on the dynamic performance of the combined rotor with different sizes is not clear.Dimensional analysis method of similarity theory was used to introduce the "size effect"existing in the process of microcrack expansion. And taking the prototype,2. 3-fold scale model and 1. 3-fold scale-up model of a heavy duty gas turbine combined rotor as the research objects,the combined rotor natural frequency drift were analyzed in the case of initial microcracks varying with combined rotor size. The results show that there is comparatively large deviation when using the ordinary Paris formula to analyze the natural frequency drift of the different size combined rotors caused by microcrack expansion. There is a certain correlation between the change of dynamic performance and the size of combined rotor considering microcracks.